Selected Papers from the 6th Fábos Conference on Landscape and Greenway Planning (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book contains five research articles and one review article derived from the 6th Fabos Conference on Greenway Planning held at the University of Massachusetts, Amherst, in April of 2019. Specific topics covered include greenway planning and analysis for urban morphology, typology, climate change impact and recreational and health usage, in addition to historic greenway restoration. All the articles illustrate multidisciplinary approaches for analyzing urban greenway functions within expanding and contracting cities.